A temporal stable isotopic (δ18O, δD, d‐excess) comparison in glacier meltwater streams, Taylor Valley, Antarctica. Issue 17 (21st July 2017) - Leslie, Deborah L.; Welch, Kathleen A.; Lyons, W. Berry
Abstract: In this paper, we describe the importance of hyporheic dynamics within Andersen Creek and Von Guerard Stream, Taylor Valley, Antarctica, from the 2010–2011 melt season using natural tracers. Water collection started at flow onset and continued, with weekly hyporheic‐zone sampling. The water δ 18 O and δD values were isotopically lighter in the beginning and heavier later in the season. D‐excess measurements were used as an indicator of mixing because an evaporative signature was evident and distinguishable between 2 primary end‐members (glacier meltwater and hyporheic zone). Hyporheic‐zone influence on the channel water was variable with a strong control on streamwater chemistry, except at highest discharges. This work supports previous research indicating that Von Guerard Stream has a large, widespread hyporheic zone that varies in size with time and discharge. Andersen Creek, with a smaller hyporheic zone, displayed hyporheic‐zone solute interaction through the influence from subsurface hypersaline flow. Overall, the evolution of Taylor Valley hyporheic‐zone hydrology is described seasonally. In mid‐December, the hyporheic zone is a dynamic system exchanging with the glacier meltwater in the channel, and with diminishing flow in January, the hyporheic zone drains back into the channel flow also impacting stream chemistry. This work adds new information on the role of hyporheic zone–stream interaction in these glacier meltwater streams.